The effect of motor activity on improved memory andemotional well-being in elderly women. (Influencia de la actividad motora en la mejora de la memoria y del estado de ánimo emocional de mujeres mayores). - Alberto Fernández Lucas; Marta Zubiaur González; Mª Carmen Requena Hernández (Ramón Cantó Alcaraz, 2008)
Abstract This study researches the effect of a wide range of different types of intervention (cognitive versus cognitive + motor versus non-intervention) on the memory and mental state of elderly women complaining of memory loss and leading a sedentary life. Subjects (N=102, 80% women, age M/SD = 76/5 years) were distributed randomly into the three treatment groups. The cognitive training consisted of attention exercises, language, association of ideas and problem solving while the motor training consisted of proprioceptive and dynamic exercises related to the body schema, balance and movement coordination. The duration of the treatment period was 8 months. The Rivermead Behavioural Memory Test (RBMT) and the Yesavage´s Geriatric Scale of Depression (GDS) were applied before and after the treatment period. Results showed improvements associated with both interventions but deterioration in the control group. However, only the cognitive-motor group showed relevant improvement according to the above-mentioned tests. Results suggest that combined cognitive-motor intervention is more promising than the simply cognitive in improving memory function and the state of well-being in women who complained of subjective memory loss, and that both techniques are effective when compared with non-intervention. Resumen Este estudio investiga el efecto de diversos tipos de intervención (cognitiva versus cognitiva + motora versus no intervención) en la memoria y el estado de ánimo emocional en mujeres mayores con quejas de memoria y con una vida pasiva. Los sujetos (N=102, 80% mujeres, edad M/SD = 76/5 años) se distribuyeron de forma aleatoria en los tres grupos de tratamiento. El entrenamiento cognitivo consistió en ejercicios de atención, lenguaje, asociación de ideas y resolución de problemas. El entrenamiento motor consistió en ejercicios propioceptivos y dinámicos relacionados con el esquema corporal, el equilibrio y la coordinación de movimientos. La intervención se llevó a cabo durante 8 meses. Se aplicaron el Test Conductual de Memoria Rivermead (RBMT) y la Escala Geriátrica de Depresión de Yesavage (GDS) antes y después. Los resultados demuestran mejorías asociadas a ambas intervenciones y deterioro en el grupo de control. Sin embargo, sólo el grupo de intervención cognitiva-motora muestra una mejoría relevante según las pruebas citadas. Los resultados sugieren que la intervención combinada cognitiva-motora es más prometedora que la intervención simplemente cognitiva para mejorar la función de la memoria y del estado de ánimo en mujeres con pérdidas de memoria subjetivas, y que las dos son eficaces en comparación con la no intervención.